HOW DOES STUDENTS RESEARCH SKILLS ENCOURAGED IN BIOLOGY LEARNING TEXT BOOK? (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2021)
This study aimed to identify the provision and the levels of research skills in the 10th grade Biology Textbook. The sample is a biology textbook named Biologi untuk Kelas X SMA/MA. The units analyzed are only focus on 4 components books, namely Diskusi; Kuis Bio; Tugas Mandiri; and Aktivitas. Research skills referred to the Research Skills Development (RSD) framework developed by Willison and O’Regan. The result of the analysis stated that about 66.21 % of component books identified providing students to have research skills. As for the level of Research Skills, most of it is in level 1 (Prescribed Research).
Keywords: research skills; research skills development; biology learning